The Influence of Financial Literacy and Lifestyle on Consumptive Behavior in The Lowokwaru Sub-District Community - Yuliana, Veny; Rahadjeng, Erna Retna; Lestari, Novi Puji (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This research aims to determine the influence of financial literacy and lifestyle, both partially and simultaneously, on consumer behavior in the people of Malang City. The population in this study were people who lived in Tlogomas Village, Lowokwaru District, Malang City, East Java, totaling 894 people. Sampling used the slovin formula and obtained 100 people. The data collection method is by distributing questionnaires to respondents online via the Google form. Data analysis in this research uses research instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing. The results of this research show that financial literacy has a positive and significant effect on consumptive behavior, lifestyle has a positive and significant effect on consumptive behavior, and simultaneously financial literacy and lifestyle have a positive and significant effect on consumptive behavior.